Seismic architecture of Yongle isolated carbonate platform in Xisha Archipelago, South China Sea - Liu, Gang; Wu, Shiguo; Gao, Jinwei; Zhang, Hanyu; Han, Xiaohui; Qin, Yongpeng; Tian, Liyan; Chen, Wanli; Huang, Xiaoxia (Frontiers in Earth Science, 2023)
This study presented recently reprocessed multi-channel seismic data and multi-beam bathymetric map to reveal the geomorphology and stratigraphic architecture of the Yongle isolated carbonate platform in the Xisha Archipelago, northwestern South China Sea. Our results show that the upper slope angles of Yongle carbonate platform exceed 10° and even reach to ~32.5° whereas the lower slope angles vary from 0.5° to 5.3°. The variations of slope angles show that margins of Yongle Atoll belong to escarpment (bypass) margins to erosional (escarpment) margins. The interior of carbonate platform is characterized by sub-parallel to parallel, semi-continuous to continuous reflectors with medium- to high-amplitude and low- to medium-frequency. The platform shows a sub-flat to flat-topped shape in its geometry with aggradation and backstepping occurring on the platform margins. According to our seismic-well correlation, the isolated carbonate platform started forming in Early Miocene, grew during Early to Middle Miocene, and subsequently underwent drowning in Late Miocene, Pliocene and Quaternary. Large-scale submarine mass transport deposits are observed in the southeastern and southern slopes of Yongle Atoll to reshape the slopes since Late Miocene. The magmatism and hydrothermal fluid flow pipes around the Yongle Atoll have been active during 10.5–2.6 Ma. Their activity might intensify dolomitization of the Xisha isolated carbonate platforms during Late Miocene to Pliocene. Our results further suggest that the Yongle carbonate platform is situated upon a pre-existing fault-bounded block with a flat pre-Cenozoic basement rather than a large scale volcano as previously known and the depth of the basement likely reached to 1400 m, which is deeper than the well CK-2 suggested.